VEGF and NLR as Diagnostic Biomarkers in Malignant, Non-Malignant, and Tuberculosis Pleural Effusion Patients (Majalah Kedokteran Bandung, 2026)
Differentiating malignant from non-malignant pleural effusions, as well as distinguishing malignancy from tuberculosis, remains challenging and carries significant diagnostic and therapeutic implications. This study aimed to analyze vascular endothelial growth factor (VEGF) level and the neutrophil-to-lymphocyte ratio (NLR) in pleural fluid as potential diagnostic biomarkers. A cross-sectional analytical observational study conducted using purposive sampling. A total 110 patients were divided into three groups, and  VEGF and NLR levels were measured from pleural fluid samples. Data were analyzed using the Kruskal–Wallis test followed by Dunn's post-hoc test. Results demonstrated that VEGF levels among the three groups differed significantly (p=0.000). The VEGF level was highest in the malignant pleural effusion (MPE) group at 6,916.80 pg/mL, compared with 4,544.49 pg/mL in the Non-MPE (NMPE) and 1,936.61 pg/mL in the tuberculosis group. Receiver operating characteristic (ROC) curve analysis showed that VEGF had the highest diagnostic accuracy in differentiating malignant from non-malignant effusion (AUC: 80.8%, p=0.000), and for distinguishing malignant from tuberculosis effusion (AUC: 76.8%; p=0.000). In contrast, NLR did not demonstrate meaningful diagnostic performance. Although the VEGF levels were elevated across all groups (MPE, NMPE, and tuberculosis), they were significantly higher in malignant effusions. VEGF demonstrated high sensitivity and specificity as a diagnostic biomarker for differentiating MPE, NMPE, and tuberculosis-related effusions. Thus, VEGF shows good potential as a diagnostic biomarker for identifying MPE, whereas NLR does not demonstrate usefulness as a diagnostic biomarker.
Keywords: Malignant pleural effusion; neutrophil to lymphocyte ratio; vascular endothelial growth factor